Exploring the Factors Affecting the Online and Offline Impulse Buying Behaviour of the Millennium Generation - Ammar Hussain; Raza Saleem Khan; Naeem Ahmed Tahir (Journal of Management Practices, Humanities and Social Sciences, 2023)
The study aims to explore various elements that affect the impulse buying behaviour of the millennial generation during online and offline purchasing. In this study, data was collected through semi-structured interviews with nine respondents and analyzed through thematic analysis. Results indicate that during offline purchasing attractive product display increases the likelihood of impulse buying, and crowd affects impulse buying both negatively and positively. Physical assessment of the product appeared as the main reason for doing the offline shopping. While on the other hand in a virtual environment, ease of transition increases the likelihood of impulse purchases. The results further disclose that individuals are engaged in buying impulsively without thinking about their economic condition and they do extra purchases when their mood is not good and when they are with friends